Thermo-oxidative Degradation of High Density Polyethylene Containing Manganese Carboxylate - Maryudi, M.; Anwaruddin, Hisyam; R. M., Yunus; Beg, M. D. H. (IJERA, 2013)
This paper reports the study of utilization of manganese laurate for accelerating the degradation process of high density polyethylene (HDPE). Specimens were prepared by loading manganese laurate from 0 to 1%(w/w) in HDPE resins using twin screw extruder followed by injection molding. Thermal treatment was performed at 70C, for maximum duration of 1000 hours to examine the thermooxidative degradation of HDPE blends. Tensile testing, FTIR analysis, molecular weight analysis, melt flow index (MFI) analysis, differential scanning calorimetry (DSC) test, thermogravimetric analyzer (TGA) test, were carried out to assess the changes during treatment. The results reveal that sample containing manganese laurate are readily to undergo thermo-oxidative degradation under temperature condition of 70 C. Tensile strength and elongation at break decreased during treatment. Pure and HDPE containing 1 % of manganese laurate (ML10) samples have lost about 11.74 and 43.33% of tensile strength, and about 16.21 and 55.85 % of elongation at break respectively. FTIR traces exhibited that carbonyl group’s peak in the region 1700-1800 cm-1 arise during thermal treatment as the result of oxidation. Average molecular weights were found to decrease about 16.12 and 67.51% from their initial value for pure and ML10 samples respectively, and consequently MFI increased significantly. Thermal stability and melting temperature were found to shift to lower temperature, while crystallinity generally increased. The degradation rate of HDPE increased by increasing the amount of manganese laurate incorporated.